2022
DOI: 10.1038/s41409-022-01885-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential of TCR sequencing in graft-versus-host disease

Abstract: Graft-versus-host disease (GvHD) remains one of the major complications following allogeneic haematopoietic stem cell transplantation (allo-HSCT). GvHD can occur in almost every tissue, with the skin, liver, and intestines being the mainly affected organs. T cells are implicated in initiating GvHD. T cells identify a broad range of antigens and mediate the immune response through receptors on their surfaces (T cell receptors, TCRs). The composition of TCRs within a T cell population defines the TCR repertoire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…In these studies, however, data interpretation is complicated by limited sampling and information regarding antigen specificities or alloreactivity of the sequenced TCRs. 44 , 45 , 46 Koyama et al 46 showed that the majority of dominant TCRs found in GVHD-affected skin tissues were also detectable in blood, including the TCR of 1 of 2 confirmed alloreactive T-cell clones. However, Sacirbegovic et al 47 showed in mice that TCR repertoires in affected GVHD tissues compared with blood increasingly diverge in time because of T-cell influx from blood in early GVHD and subsequent maintenance by tissue-resident progenitor-like T cells in late GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, however, data interpretation is complicated by limited sampling and information regarding antigen specificities or alloreactivity of the sequenced TCRs. 44 , 45 , 46 Koyama et al 46 showed that the majority of dominant TCRs found in GVHD-affected skin tissues were also detectable in blood, including the TCR of 1 of 2 confirmed alloreactive T-cell clones. However, Sacirbegovic et al 47 showed in mice that TCR repertoires in affected GVHD tissues compared with blood increasingly diverge in time because of T-cell influx from blood in early GVHD and subsequent maintenance by tissue-resident progenitor-like T cells in late GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Because the TCR repertoire is highly dynamic in the early post-aHSCT setting as the immune system recovers, characterizing the TCR repertoire may allow prediction of clinical outcomes or toxicities. 10 Thus, a combination of these modalities could allow us to find new insights for understanding and managing GI-GvHD.…”
Section: Main Textmentioning
confidence: 99%